Learning processes in early and rapid internationalization – a theoretical journey and future pathways - Appiah, Emmanuel Kusi (Emerald, 2026)
Purpose This review identifies and categorizes the key theories applied in the extant literature, analyses how those theories contribute to understanding the dynamics and mechanisms of learning in early internationalizing firms (EIFs), highlights theoretical gaps, and proposes directions for future research to advance knowledge in the field international marketing. Design/methodology/approach It reports on a systematic literature review conducted to collate and synthesize the prior research on the theoretical foundations of learning processes in EIFs. Findings The review identified new research areas based on existing theories, emphasizing the need to expand and refine established frameworks to explore underdeveloped dimensions. It also highlighted emerging theoretical perspectives, introducing alternative lenses to uncover novel insights and address current knowledge gaps. Research limitations/implications While this review primarily focuses on EIFs, its findings may not fully capture the factors affecting other firm types. Expanding future research to explore learning mechanisms across diverse internationalization trajectories, such as firms with gradual expansion models or established multinational corporations, would provide deeper insights and broaden the applicability of the theoretical perspectives. Practical implications International marketers and entrepreneurs could leverage this review to strategically build networks to bolster successful market entry and strengthen learning mechanisms. The strategy could include pre-entry collaboration with experienced international firms that offer critical market insights, regulatory guidance, and operational support, as well as external relationships, such as those with industry partners, mentors or local distributors that help overcome knowledge gaps and mitigate risks in unfamiliar foreign markets. Originality/value It emphasizes the dynamic nature of learning in EIFs and its critical role in driving market adaptability, innovation, and international performance in global settings.
Keywords: Early internationalization; Early internationalizing firms; Theoretical foundation; International new venture; Born-global firm; fi=Kansainvälinen liiketoiminta|en=International Business|